Activation of trace amine‐associated receptor 1 attenuates nicotine withdrawal‐related effects. (25th June 2021) - Wu, Ruyan; Liu, Jianfeng; Johnson, Bernard; Huang, Yufei; Zhang, Yanan; Li, Jun‐Xu
Abstract: Nicotine addiction is a leading avoidable brain disorder globally. Although nicotine induces a modest reinforcing effect, which is important for the initial drug use, the transition from nicotine use to nicotine addiction involves the mechanisms responsible for the negative consequences of drug abstinence. Recent study suggested that trace amine‐associated receptor 1 (TAAR1) is a promising pharmacological target for the modulation of positive reinforcing effects of nicotine. However, whether TAAR1 plays a part in the negative reinforcement of nicotine withdrawal remains to be determined. Here, using a long‐access (LA) self‐administration model, we investigated whether LA rats show increased nicotine intake and withdrawal symptoms in comparison with saline and ShA rats and then tested the effect of TAAR1 partial agonist RO5263397 on nicotine withdrawal effects. We found that rats from long‐access group showed significant abstinence‐induced anxiety‐like behaviour, mechanic hypersensitivity, increased number of precipitated withdrawal signs and higher motivation for the drug, while rats from short‐access did not differ from saline group. TAAR1 partial agonist RO5263397 significantly reduced the physical and motivational withdrawal effects of nicotine in LA rats, as reflected by increased time spent on the open arm in the elevated plus maze (EPM) test, normalized paw withdrawal threshold, decreased withdrawal signs and motivation to self‐administer nicotine. This study indicates that activation of TAAR1 attenuates the negative‐reinforcing effects of nicotine withdrawal and further suggests TAAR1 as a promising target to treat nicotine addiction. Abstract : Role of trace amine‐associated receptor 1 (TAAR1) in nicotine withdrawal is unknown. This study trained rats to self‐administer nicotine to establish physical dependence and tested the effects of a TAAR1 agonist on nicotine withdrawal‐related effects. The TAAR1 agonist RO5263397 significantly reduced all withdrawal‐related behavioural effects.